A Unique Case of Poorly Differentiated Neuroendocrine Carcinoma With Brain and Bilateral Adrenal Metastases - Carla J. El Hajj Mouawad; Francois Georges Kamar (Cancer Reports)
ABSTRACT Background Small‐cell carcinoma is a highly malignant neuroendocrine neoplasm arising from cells of the endocrine and nervous systems, and usually of bronchogenic origin. When found in the retroperitoneum, these malignant cells are extremely rare and are mainly metastatic tumors. Adrenal glands are unusual sites of distant metastases, the common primary being bronchopulmonary and gastroenteropancreatic neuroendocrine tumors (NETs). We report a case of poorly differentiated neuroendocrine carcinoma (NEC) that was initially discovered in both adrenal glands. Case Our patient was a 68‐year‐old woman who presented with articular pain and severe chronic hemolytic anemia. Her workup comprised a contrast‐enhanced computed tomography (CT) scan of the chest, abdomen, and pelvis, revealing a left adrenal mass lesion measuring 14 × 9 cm, and a concomitantly smaller right adrenal mass lesion arising from the gland and measuring 4 × 2 cm. In view of the size of the left adrenal mass we elected to offer her a complete resection. The patient therefore underwent a laparoscopic adrenalectomy. Histopathological examination of the specimen revealed a high‐grade, poorly differentiated NEC of the adrenal gland, small‐cell type, with tumor necrosis. A baseline evaluation comprised an FDG‐PET CT scan revealing the contralateral adrenal tumor, which was also partially resected to leave the patient with some functional adrenal tissue and not render her Addisonian. Although we found no pulmonary primary, a bleb was seen on chest CT that we hypothesized was possibly a burn‐out primary in the setting of an immunogenic tumor. Conclusion Surgery played a vital role in our case followed by combination of chemoimmunotherapy as per present recommendation of a small‐cell tumor especially since the patient presented with atypical clinical manifestations.